Laser-Inscribed Stress-Induced Birefringence of Sapphire - Fan, Hua (Nanomaterials (Basel), 2019)
Birefringence of [Formula: see text] is demonstrated inside cross-sectional regions of 100 [Formula: see text] m, inscribed by axially stretched Bessel-beam-like fs-laser pulses along the c-axis inside sapphire. A high birefringence and retardance of [Formula: see text] at mid-visible spectral range (green) can be achieved using stretched beams with axial extension of 30–40 [Formula: see text] m. Chosen conditions of laser-writing ensure that there are no formations of self-organized nano-gratings. This method can be adopted for creation of polarization optical elements and fabrication of spatially varying birefringent patterns for optical vortex generation.